Productivity and Nutrient Content of the Second Regrowth Alfalfa (Medicago Sativa L.) with Different Photoperiod and Dolomite - Bambang Suwignyo; F.X. Dika Kurniawan; Nilo Suseno; Ristianto Utomo; Bambang Suhartanto (ANIMAL PRODUCTION, 2020)
The study was conducted to identify the effect of lighting duration and dolomite addition on the vegetative growth of alfalfa plants in second regrowth phase. The experiment was conducted in the greenhouse of the Laboratory of Forage and Pasture Science, Faculty of Animal Science, Universitas Gadjah Mada. It used a completely randomized design with 3x3-factorial using two factors and three replications. The first factor was lighting duration (C) with 3 levels (C0 = 12 hours, C1 = 14 hours, and C2 = 16 hours). The second factor was dolomite addition (D) with 3 levels (D0 = 0 ton/ha, D1 = 6 ton /ha, and D2 = 12 ton/ha). The results showed a significant effect so Duncan Multiple Range Test (DMRT) followed at 5% and 1% levels. The observed variables were plant height, the number of plant branches, the number of plant leaves, fresh forage production, and the chemical content of the plants in the form of dry matter (DM) and organic matter (OM). The addition of dolomite significantly affected the number of the plant branches, the number of plant leaves and the dry matter of the plants. A significant correlation was found between the two treatments and the number of leaves (C2D2) and a correlation was between the treatment and dry matter (C1D2).